Bean based recipe booklet: promoting the consumption of beans in a variety of ways - National Food and Nutrition Commission; Zambia Agriculture Research Institute (Pan-Africa Bean Research Alliance, 2014)
This booklet is designed for extension officers to help them provide step by step instructions to communities and households on how to prepare and consume all types of beans using various recipes. The use of various recipes is vital in promoting the consumption of bean. The booklet therefore provide recipes for preparing bean purees of various types, bean flour for preparing porridges and other products. The purees and porridge are good for children and other population groups that are not able to eat solid food. The recipes are presented in the following order; Bean purees, Bean flour and porridge, Bean snacks, Bean dishes and Bean soups.